Inventory Of Environmental Issues Related To The Utilization Of Natural Resources In Coastal Areas Case Study : Wedung Sub-districts, Demak Regency - Eppy Yuliani (International Conference on Coastal and Delta Areas, 2017)
Wedung Sub-districts, is one of the locations in the southwestern coastal estuary of Demak Regency. Potential natural resources, mainly salt encryption pond, agriculture, characters livestock. The harmful socio-economic life of the community is dominated the United States farmers' and market traders. many environmental problems faced by the local community. The purpose of this research is to conduct an inventory of environmental issues related to the utilization of natural resources. The methodology employed is a qualitative deductive rationalist approach, with descriptive analysis techniques. Research variables include natural resource types and environmental issues. the conclusion of the research is the natural resources of the coastal area of Wedung Sub-districts covering marine resources producing fishfinder catch and people's salt encryption . Agriculture with the main production of rice. Environmental issues encountered include abrasion, flooding, rob, beach abrasion, drought. Keywords: environmental issues, coastal areas.